Evaluation and Comparison of Different Methods for Improving Fault Ride-Through Capability in Grid-Tied Permanent Magnet Synchronous Wind Generators. (18th January 2023) - Mahmoud, Mohamed Metwally; Atia, Basiony S.; Esmail, Yahia M.; Bajaj, Mohit; Mbadjoun Wapet, Daniel Eutyche; Ratib, Mohamed Khalid; Biplob Hossain, Md.; AboRas, Kareem M.; Abdel-Rahim, Abdel-Moamen M.
Abstract : Several advantages make wind-driven permanent magnet synchronous generators (PMSGs) very promising in the wind energy market, especially their fault ride-through capabilities. With the high penetration levels of today, both the grid and wind power (WP) systems are being affected by each other. Due to grid faults, the DC-bus in PMSG systems typically experiences overvoltage, which can negatively affect the generator parameters and trip the system. However, advancements in power electronics, control systems, fault limiters, FACTS, and energy storage technology make it possible to find and design satisfactory solutions and approaches. The most recent FRTC-improving techniques are mainly modified or external techniques based on controllers in PMSG-based WP. This paper evaluates the in-depth schemes of FRTC, introducing the underlying theory and traits of the different approaches to highlight the advantages and drawbacks of each. Five scenarios of DC-link voltage under zero-grid voltage are carried out by using the MATLAB SIMULINK program to assess the FRTC methods. This study shows that external device-based approaches can be efficient, but some of them are expensive, thus updated controller methods are recommended to cut costs. Research findings of this study are expected to support the deployment of FRTC technologies, as well as provide valuable input into WP research on grid integration.